Origin and Evolution of the Gene Family of Proteinaceous Pheromones, the Exocrine Gland-Secreting Peptides, in Rodents. (22nd September 2020) - Niimura, Yoshihito; Tsunoda, Mai; Kato, Sari; Murata, Ken; Yanagawa, Taichi; Suzuki, Shunta; Touhara, Kazushige
Abstract: The exocrine-gland secreting peptide (ESP)gene family encodes proteinaceous pheromones that are recognized by the vomeronasal organ in mice. For example, ESP1 is a male pheromone secreted in tear fluid that regulates socio-sexual behavior, and ESP22 is a juvenile pheromone that suppresses adult sexual behavior. The family consists of multiple genes and has been identified only in mouse and rat genomes. The coding region of a mouse ESP gene is separated into two exons, each encoding signal and mature sequences. Here, we report the origin and evolution of the ESP gene family. ESP genes were found only in the Muridea and Cricetidae families of rodents, suggesting a recent origin of ESP genes in the common ancestor of murids and cricetids. ESP genes show a great diversity in number, length, and sequence among different species as well as mouse strains. Some ESPs in rats and golden hamsters are expressed in the lacrimal gland and the salivary gland. We also found that a mature sequence of an ESP gene showed overall sequence similarity to the α-globin gene. The ancestral ESP gene seems to be generated by recombination of a retrotransposed α-globin gene with the signal-encoding exon of the CRISP2 gene located adjacent to the ESP gene cluster. This study provides an intriguing example of molecular tinkering in rapidly evolving species-specific proteinaceous pheromone genes.